2016
DOI: 10.19113/sdufbed.23967
|View full text |Cite
|
Sign up to set email alerts
|

Çoklu Melez Parsellerinde Yer Alan Yonca Genotiplerinin Tohum Tutma Özelliklerinin Belirlenmesi

Abstract: Anahtar KelimelerYonca, Tohum verimi, Göller yöresi Özet: Bu araştırma, göller yöresinden toplanmış 10 adet yonca (Medicago sativa L.) genotipinde tohum tutma özellikleri ve bazı verim unsurlarını belirlemek amacıyla 2014 yılında Süleyman Demirel Üniversitesi Ziraat Fakültesi deneme arazisinde yürütülmüştür. Araştırmada kullanılan bitkisel materyaller içerisinde, en uzun bitki boyu (103.22 cm) 6 nolu genotipten, en yüksek bitkide sap sayısı (55.44 adet/bitki), salkımda çiçek sayısı (62.33 adet) ve bitki başına… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
(2 reference statements)
0
1
0
Order By: Relevance
“…In terms of years, the average plant height (100.9 determined in 2021 higher than the average plant height determined in 2020 (94.4 cm). When look at the previous studies on the plant height in alfalfa; it has been reported that it is detected between 79-100 cm in Bornova conditions [9], 57.70-79.40 cm in Northern Cyprus conditions [10], 74.8-86.8 cm in Izmir conditions [11], 85.10-93.20 cm in Tokat-Kazova conditions [12], 66.61-101.28 cm in Antalya conditions [13], 80.33-103.22 cm in Goller Region [14], 76.3-90 cm in Yozgat ecological conditions [15] and 59.3-109.3 cm in Bingöl conditions [16]. It is seen that the 87.6-106.2 cm alfalfa height obtained in this study is close and similar to the plant heights obtained in these studies.…”
Section: Plant Height (Cm)mentioning
confidence: 99%
“…In terms of years, the average plant height (100.9 determined in 2021 higher than the average plant height determined in 2020 (94.4 cm). When look at the previous studies on the plant height in alfalfa; it has been reported that it is detected between 79-100 cm in Bornova conditions [9], 57.70-79.40 cm in Northern Cyprus conditions [10], 74.8-86.8 cm in Izmir conditions [11], 85.10-93.20 cm in Tokat-Kazova conditions [12], 66.61-101.28 cm in Antalya conditions [13], 80.33-103.22 cm in Goller Region [14], 76.3-90 cm in Yozgat ecological conditions [15] and 59.3-109.3 cm in Bingöl conditions [16]. It is seen that the 87.6-106.2 cm alfalfa height obtained in this study is close and similar to the plant heights obtained in these studies.…”
Section: Plant Height (Cm)mentioning
confidence: 99%